1995
DOI: 10.1088/0953-8984/7/40/009
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of the interaction of methyl thiol and dimethyldisulphide with Ni(111)

Abstract: A combination of "ex-edge and surface extended x-ray absorption fine stmcture (NEXAFS and SEXAFS), normal incidence x-ray standing wavefield absorption (NIXSW) and (laboratory-based) x-ray photoelectron spectroscopy and diffraction (XPS and XPD) has been used to investigate the local phases and associated structures resulting from the interaction of methylthiol (CH3SH) and dimethyldisulphide ((CH3S)x-DMS) with Ni( 1 I I). The interaction was followed by adsorbing at low temperature and observing the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Above room temperature methane desorption has been observed, leaving S on the surface. For lower coverage it was suggested [37] that the adsorption of CH 3 S induces a surface layer reconstruction similar to that reported for methane-thiolate adsorption on Cu(111) [38] and for the adsorption of atomic sulfur on Ni(111) [39]. For the more open Ni(100) surface it was reported [40] that alkanethiols start to decompose at low temperatures to form adsorbed thiolates and that further heating results in the formation and desorption of alkanes, olefins and hydrogen and leaves sulfur adsorbed on the surface.…”
Section: Introductionsupporting
confidence: 53%
“…Above room temperature methane desorption has been observed, leaving S on the surface. For lower coverage it was suggested [37] that the adsorption of CH 3 S induces a surface layer reconstruction similar to that reported for methane-thiolate adsorption on Cu(111) [38] and for the adsorption of atomic sulfur on Ni(111) [39]. For the more open Ni(100) surface it was reported [40] that alkanethiols start to decompose at low temperatures to form adsorbed thiolates and that further heating results in the formation and desorption of alkanes, olefins and hydrogen and leaves sulfur adsorbed on the surface.…”
Section: Introductionsupporting
confidence: 53%
“…An alternative method is demonstrated in Fig. 3B, Fernfindez et al [18] have shown that the methyl group in CHaS on Ni(lll) at 100 K is tilted toward the surface. Assuming that the orientation is also azimuthally averaged, the C Is photoemission is not expected to show any angular anisotropy.…”
Section: X-ray Photoelectron Diffractionmentioning
confidence: 99%
“…5 This is consistent with studies of methanethiolate species chemisorbed onto W, Ru, Ni, Cu, and Ag single-crystal surfaces. [28][29][30][31][32][33] detected in lower coordination sites than the hollow sites (e.g., bridge sites). 28,29 In all cases where the S 2p3/2 BE was measured it was observed to decrease in the order unbound thiol or disulfide > thiolate in hollow site > thiolate in low-coordination site.…”
Section: Introductionmentioning
confidence: 99%